STATUS KEBERLANJUTAN PENGOLAHAN AGROINDUSTRI TEH KELOMPOK TANI BAROKAH DI KECAMATAN CIWIDEY KABUPATEN BANDUNG PROVINSI JAWA BARAT - Bima Mulia; Lucyana Trimo; Eti Suminartika (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The tea commodity has an important role in the Indonesian economy, namely as an absorption of labor, a source of income for farmers, foreign exchange, encouraging agro-industrial development and environmental conservation. The purpose of this study is to determine and evaluate the sustainability status of the Barokah farmer group's tea plantations. The research was conducted in the tea plantation agro-industry of the Barokah farmer group, Ciwidey District, Bandung Regency. The data used in this study consisted of primary data and secondary data. Primary data used in this study were obtained from direct observations in the field and direct interviews with the object of research. Secondary data in this study were obtained from related parties such as the Barokah Farmer Group, the people's tea agro-industry, the Lebak Muncang Village Office. Apart from what has been mentioned above, researchers also use secondary data from literature studies, journals, previous research. The analysis method uses multidimensional scaling (MDS). The results showed the evaluation results of the agro-industrial sustainability of the Barokah farmer groups' tea plantations, showing all dimensions, namely ecological, economic, social, institutional and technological in the sufficient category.